Organizational Commitment as an Antecedent of Organizational Citizenship Behavior: A Study of Nursing Staff Working in Select Government Hospitals in Sidama Regional State, Southern Ethiopia - Anisa, Mengistu; Malhotra, Meenakshi (Gyan Management Journal, 2023)
Successful organizations have employees who go beyond their formal job  tasks and freely give their time and liveliness to succeed at the assigned  job. Such humanity is neither prescribed nor required, yet it contributes to  the smooth functioning of the organization. This study aimed to examine  organizational commitment as an antecedent of Organizational Citizenship  Behavior a study of nursing staff working in Select Government Hospitals  in Sidama Regional State, Southern Ethiopia. Methodologically, the study  has been mainly depending on the primary source of data obtained  through nursing staff work in the Sidama regional state of southern  Ethiopia. Among 1900 total nursing staff in the four hospitals in this study  210 samples have been considered for the analysis based on 204 of the  respondents who responded to the questionnaire. In this study, SPSS and  AMOS version 21 were applied for analysis purposes. The measurement  model based on CFA reveals that the items are fitted for the construct after  some of the items are removed as a result of low loadings. The structural  equation model shows the positive relationship between the variables  under the study. Based on the finding obtained theoretical and practical  implications provided through the management of the hospitals need to  have enhanced organizational commitment of nursing staff to reciprocate  the result. Furthermore, the study opts for future researchers based on the  gap mentioned.
Keywords: Affective Commitment; Continual Commitment; Normative Commitment; Organizational Citizenship Behavior